BORDER AREA ECONOMIC DEVELOPMENT STRATEGY: A SUSTAINABLE APPROACH - Indah Sulistiani; Soni Suardi; Syarifuddin (CV. Adiba Aisha Amira, 2025)
Border regions are currently entering a new paradigm of regional development. As a region that emerged as a result of globalization and policy decentralization, there has been a shift in the security paradigm towards prosperity. Characteristics that are different from other regions (immobility of production factors, transaction costs and delays, different economic systems, institutional issues, zoning and the role of the informal sector) encourage the economic function of the region on the internal and external side. The economic perspective in border areas tends to improve along with this paradigm change. Facing the challenges of economic development involves identifying the main problems that affect economic growth and progress, as well as formulating appropriate strategies and policies to overcome these problems. This involves cooperation between government, the private sector, civil society, and international institutions to achieve sustainable economic development. The economic development strategy for border areas is related to efforts to stimulate economic growth. This strategy supports existing policies and includes planning strategies in the medium and long term. These strategies include: encouraging conducive and operational regulations in the field of economic development in border areas, compiling a road map for effective and operational spatial planning, improvising infrastructure development that is responsive to needs (hard & soft infrastructure), increasing the role of leading sectors and encouraging sectors others in growth, increasing attention to the sustainability of development and development of Human Resources, facilitating internal and external trade.